Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/jfbc.12696
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of non‐anthocyanin polyphenol accumulation in the berry skins of muscadine and European grapes during ripening in China

Abstract: The non‐anthocyanin polyphenol accumulation in the berry skins of muscadine grapes from South China during ripening was investigated, in comparison to European grapes, for two consecutive years, using ultra‐performance liquid chromatography tandem triple quadrupole time‐of‐flight mass spectrometry. A total of 121 components were tentatively identified, consisting of 48 ellagic acids and precursors (EP), 38 flavonols, 20 hydroxybenzoic acids, 6 hydroxycinnamic acids, 5 flavan‐3‐ols, and 4 stilbenes. EP (mostly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
3
1
0
Order By: Relevance
“…The evolution pattern seen for catechin was similar to that observed for trans-caftaric acid, which was also consistent with previous investigations that demonstrated catechin levels to be 550 µg/100 g FW around 10 days before harvest, but they dropped to 440 µg/100 g FW at harvest [22]. Furthermore, large year-to-year variations have been seen for other flavanol monomers (epicatechin and gallate derivatives), where a decline close to harvesting has also been recorded [23]. The results on V. vinifera cv.…”
Section: Non-anthocyanin Polyphenolssupporting
confidence: 90%
See 2 more Smart Citations
“…The evolution pattern seen for catechin was similar to that observed for trans-caftaric acid, which was also consistent with previous investigations that demonstrated catechin levels to be 550 µg/100 g FW around 10 days before harvest, but they dropped to 440 µg/100 g FW at harvest [22]. Furthermore, large year-to-year variations have been seen for other flavanol monomers (epicatechin and gallate derivatives), where a decline close to harvesting has also been recorded [23]. The results on V. vinifera cv.…”
Section: Non-anthocyanin Polyphenolssupporting
confidence: 90%
“…The findings of other studies are in concurrence, with one study reporting trans-caftaric acid in Tannat grapes to reach a level of 620 µg/100 g FW ten days before harvest, and 690 µg/100 g FW at harvest [22]. However, more recent studies have indicated that there may be significant variations in hydroxycinnamate content in grapes near harvest [23].…”
Section: Non-anthocyanin Polyphenolssupporting
confidence: 65%
See 1 more Smart Citation
“…The heat block and curved desolvation line (CDL) temperature was maintained at 200 • C. Nebulizing nitrogen gas was used at a flow rate of 1.5 L/min, and as the drying gas at 75 kPa. Phenolic compounds were characterized by their MS, MS/MS spectra, UV spectra, and in comparison with previously published data [42][43][44].…”
Section: Phenolic Composition By Lc-esi-tof Ms/msmentioning
confidence: 99%
“…Muscadine grapes ( Muscadinia rotundifolia Michx .) belong to the Vitaceae family and the Muscadine genus [ 1 ], native fruit crops of the southeastern United States [ 2 ]. These grapes can thrive in high-temperature and high-humidity environments, demonstrating resistance or even immunity to various pests and diseases, such as grape downy mildew, root aphids, Pierce’s disease, and root-knot nematodes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%